A Long-Wavelength Fluorescent Squarylium Cyanine Dye Possessing Boronic Acid for Sensing Monosaccharides and Glycoproteins with High Enhancement in Aqueous Solution - Hiroyuki Nakazumi; Christa L. Colyer; Takeshi Maeda; Tara L. Massie; Shingo Saito (Sensors, 2012)
Fluorescence sensing of saccharides and glycoproteins using a boronic acid functionalized squarylium cyanine dye (“SQ-BA”) is characterized in terms of synthetic, fluorometric, thermodynamic and kinetic parameters. In our previous work, this newly synthesized dye was successfully applied to the separation and quantification of Gram-positive bacteria by capillary electrophoresis with laser-induced fluorescence detection (CE-LIF); however, the fundamental properties of the dye and its saccharide complexes still required elucidation, as presented in this paper. The dye itself forms nonemissive, soluble aggregates in aqueous solution. With the addition of a monosaccharide, the dye aggregate dissociates to form an emissive monomer accompanied by the formation of a cyclic cis-diol ester with long-wavelength emission (lex = 630 nm, lem = 660 nm). A very large fluorescence enhancement factor of 18× was observed for the sensing dye as a fructose complex at pH 10, yielding a limit of detection of 10 mM fructose. The relative order of fluorescence enhancement of SQ-BA with other monosaccharides was found to be: fructose > ribose > arabinose ≈ galactose > xylose > mannose > rhamnose > fucose ≈ glucose; and apparent affinity constants of 102.80, 102.08 and 100.86 M−1 were determined for fructose, ribose and glucose, respectively. Formation of the emissive complexes occurred within minutes, proving the kinetics of the sugar-dye interactions to be suitable for on-column labeling methods in CE-LIF. Furthermore, the sensing dye was successfully applied to glycoproteins, mucin type I–S and type III, which were detected with high sensitivity in batch aqueous solution as a result of the sugar-selective boronic acid-diol esterification as well as hydrophobic interactions.